2004
DOI: 10.1242/dev.01449
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Smad2 by PIASy is required for properXenopusmesoderm formation

Abstract: Mesoderm induction and patterning are primarily regulated by the concentration of locally expressed morphogens such as members of the TGFβsuperfamily. Smad2 functions as a transcription factor to regulate expression of mesodermal genes downstream of such morphogens. We have identified Xenopus PIASy (XPIASy), a member of the PIAS family, by yeast two-hybrid screening using Xenopus Smad2 (XSmad2) as a bait. During mesoderm induction, XPIASy is expressed in the animal half of embryos with a ventral high-dorsal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 99 publications
(128 reference statements)
2
10
0
Order By: Relevance
“…Similar effects were seen with injection of activin/ nodal pathway inhibitors such as dnSmad2 and XPIASy ( Fig. 2K; Hoodless et al, 1999;Daniels et al, 2004). These results suggested XSUMO1 is involved in the activin/nodal signal transduction pathway.…”
Section: Morphological Abnormalities Induced By Xsumo-1-mo Injectionsupporting
confidence: 72%
See 3 more Smart Citations
“…Similar effects were seen with injection of activin/ nodal pathway inhibitors such as dnSmad2 and XPIASy ( Fig. 2K; Hoodless et al, 1999;Daniels et al, 2004). These results suggested XSUMO1 is involved in the activin/nodal signal transduction pathway.…”
Section: Morphological Abnormalities Induced By Xsumo-1-mo Injectionsupporting
confidence: 72%
“…3A and B), similar to the phenotype caused by injection with dominantnegative Smad2 (dn-Smad2) or XPIASy, both negative regulators of activin/nodal signaling ( Fig. 3C; Hoodless et al, 1999;Daniels et al, 2004). These phenotypes were rescued by coinjection with myc-XSUMO-1 mRNA in a dose-dependent manner ( Fig.…”
Section: Morphological Abnormalities Induced By Xsumo-1-mo Injectionsupporting
confidence: 57%
See 2 more Smart Citations
“…Misregulation of Nodal activity can result in gastrulation defects, expansion of mesodermal lineages into the ectodermal domain, loss of head structures, and situs inversus. Furthermore, as the Nodal positive feedback loop can amplify Nodal expression and signaling, mechanisms that negatively regulate Nodal expression and activity are essential for normal development.Multiple Nodal antagonists have been identified that act at each step of the Nodal signal transduction cascade; Cerberus, Coco and Lefty/Antivin block Nodal signaling at the extracellular level (Thisse and Thisse, 1999;Piccolo et al, 1999;Cheng et al, 2000;Bell et al, 2003;Branford and Yost, 2004), whereas Dapper2, Smad7, Ectodermin and PIASy act intracellularly by stimulating receptor turnover or inhibiting Smad function (Nakao et al, 1997;Casellas and Brivanlou, 1998;Daniels et al, 2004;Zhang et al, 2004b;Dupont et al, 2005 To assess the dependence of Xnr1 and VegT activity on FoxD3, the animal pole was injected at the one-cell stage embryo with VegT (500 pg) or Xnr1 (100 pg) alone, or in combination with FoxD3MO or mismatch MO (50 ng). Animal explants were analyzed by RT-PCR at the gastrula stage (stage 11) for the expression of Brachyury (Xbra), MyoD, Goosecoid (Gsc), Xnr1 and Xnr2.…”
mentioning
confidence: 99%